Providing a Causal Model of Children’s Behavioral Disorders Based on Spiritual health Family Functioning: The Mediating Role of Life Satisfaction in Hyperactive Children’s Mothers in Tehran - Ghalenoee, Mahdiye; Asadzadeh, Hassan; Dortaj, Fariborz (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Hyperactive children can have far-reaching effects on their relationships with their family members and general atmosphere in the family by showing some behaviors such as hyperactivity, restlessness, inattention, and repulsive behaviors. This study aimed to provide a causal model of children’s behavioral disorders based on family functioning and spiritual health with the mediating role of life satisfaction in hyperactive children’s mothers. Methods: This is a descriptive correlational study in terms of the method where the relationships among the proposed variables were analyzed using structural equation modeling (SEM). The statistical population included all mothers of hyperactive children who had visited psychiatric clinics in Tehran in 2020. Two hundred fifty mothers were selected from the population using purposive sampling. The tools used in this research were: Questionnaire of children’s behavior disorder, Family Functioning Questionnaire, Spiritual health Questionnaire (SWBQ), and Questionnaire of Satisfaction with Life. The data were analyzed using Pearson’s correlation coefficient and structural equations model. Results: The results showed that life satisfaction has a positive and significant relationship with family functioning and spiritual health. The results also showed that family functioning and spiritual health have a reverse and significant relationship with children’s behavioral disorders. Furthermore, the results showed that the general path of spiritual health has a greater effect on hyperactive child’s behavioral disorders. Conclusions: The causal model of children’s behavioral disorders based on family functioning and spiritual health with the mediating role of life satisfaction has a desirable fit to decrease hyperactive behavior disorders.